First, rewrite the expression as:
#(6/12)(x^-5/x^4)(y^-5/y) => 1/2(x^-5/x^4)(y^-5/y)#
Next, use this rule of exponents to divide the #x# terms:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))# and #a^color(red)(1) = a#
#1/2(x^color(red)(-5)/x^color(blue)(4))(y^-5/y) => 1/2(1/(x^(color(blue)(4)-color(red)(-5))))(y^-5/y) =>#
#1/2(1/(x^(color(blue)(4)+color(red)(5))))(y^-5/y) => 1/2(1/(x^9))(y^-5/y) =>#
#1/(2x^9)(y^-5/y)#
Now, use these rules of exponents to divide the #y# terms:
#a = a^color(blue)(1)# and #x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))# and #a^color(red)(1) = a#
#1/(2x^9)(y^-5/y) => 1/(2x^9)(y^color(red)(-5)/y^color(blue)(1)) => 1/(2x^9)(1/y^(color(blue)(1)-color(red)(-5))) =>#
#1/(2x^9)(1/y^(color(blue)(1)+color(red)(5))) => 1/(2x^9)(1/y^6) =>#
#1/(2x^9y^6)#